Political Parties and Diaspora: A Case Study of Romanian Parties' Involvement Abroad. Issue 4 (2nd September 2020) - Borz, Gabriela
Abstract: How do parties organise for success in engaging with their diaspora? This study investigates the impact Romanian diaspora has had on national political parties. It develops an argument based on diaspora recognition, engagement and policy as implemented by old and new parties. The analysis shows that recognition of diaspora in party statutes is not a guarantee for engagement. The latter increases with the use of new online communication strategies, provided there is a demand for such communication platforms. New parties with a strong anti-corruption stance mobilise diaspora online. The policy strategy emphasises diaspora support rather than diaspora return as incumbent parties take a gradual approach based on rights and identity promotion, which increases the economic utility of the engagement. The results are based on the analysis of party statutes, governmental documents, party online communication strategies and interviews with party members.